Negotiation of meaning in face-to-face interaction among high proficiency ESL learners: 'Generation Y' gender interaction - Zainal, A.Z.; Ching, H.S. (English Language Education Publishing, 2016)
This paper analyses the linguistic output produced by high-proficiency ESL learners during face-to-face interaction. This study focuses on the Generation Y participants born in the year of 1990-1996 who have just completed secondary or higher secondary schools. Generation Y or 'Gen Y' who are born in the year of 1980-2000 are also known as 'digital natives' (Prensky, 2001), highly involved in interacting with advanced technology tools and are used to interacting with their peers within a computer-mediated environment. However, less is known about the patterns of interaction of this particular group of ESL learners in face-to-face environment. This study aims to address this gap by analysing how they negotiate meaning based on the given tasks. It also aims to find out whether gender plays a role in the interaction. The participants involved in the study were 11 females and 11 males, 22 in total and paired in a mixed-gender dyads. A decision making two-way tasks were utilized to elicit the data and the analysis of the data was based on a framework by Varonis and Gass (1985) on negotiation routine. The results revealed that the males took greater advantage of the conversation by producing semantic modification as in more 'talk' for comprehensible output whereas females utilized the conversation more for comprehensible input.